Effect of e-Government on Improving the Quality of Public Services in Serang Municipality - Sri Wahyuningsih; Rachmi Yulianti; Rethorika Berthanilla (Program Studi Administrasi Negara Universitas Serang Raya, 2021)
This study aims to find out